SISTEM PENJUALAN KREDIT ATAS JASA SEWA KAPAL PADA PT. SWAKARSA - Novi Verantika; Melinda Malau; Frangky Yosua Sitorus (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
Sales will be followed by the receipt of money. As happened in the purchase transaction, receipt of money from a sale conditional on buying and selling has been determined. In addition to income from sales, the company may receive money from other sources, such as the payment of capital owners, loan lenders, and others. Cash receipts are cash received by the company, either in the form of cash or securities that have properties can be immediately used are derived from the company as well as cash sales transactions, settlement of receivables, or other transactions that may add to the company's cash. However, cash receipts companies normally come from two main sources: cash receipts from cash sales and cash receipts of accounts receivable (credit sales). Cash receipts from cash sales is a series of business activities, which the company received a cash inflow from the sale of cash carried in a normal business. In this case, the source of cash receipts held by the company comes from cash sales, where customers immediately make a payment in cash and make purchases on credit. Customers in this case becomes one of the sources of the cycle of cash receipts from cash sales. Meanwhile, the company's receivables arising from credit sales. Sales of credit or installment are sales made by an agreement under which payments can be implemented in phases, namely: when the goods or services delivered to the buyer, the seller received the first payment (by check or transfer funds) portion of the sales price or payment (down payment) and remaining payment can be paid in stages. The cash proceeds from the sale of credit does not always go well, there are also experiencing delays (traffic) even becomes doubtful. If in accounting, accounts receivable becomes doubtful and can be removed. Meanwhile, inside the flat tax into income for the company.Keywords : Sales, Receivable, Services